2020
DOI: 10.1038/s41598-020-63846-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and behavioural markers of compassion

Abstract: The scientific study of compassion is burgeoning, however the putative neurophysiological markers of programs which actively train distress tolerance, such as Compassionate Mind Training (CMT), are less well known. Herein we offer an integrative, multi-method approach which investigated CMT at neural, physiological, self-report, and behavioural levels. Specifically, this study first assessed participants' neural responses when confronted with disappointments (e.g., rejection, failure) using two fundamental sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 50 publications
8
125
3
Order By: Relevance
“…Whilst the program of research within the present paper has been reported on previously, this examined the (neuro)physiological correlates of a brief, two-week compassion training paradigm 4 Participants provided informed and voluntary, written and/or electronic consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the program of research within the present paper has been reported on previously, this examined the (neuro)physiological correlates of a brief, two-week compassion training paradigm 4 Participants provided informed and voluntary, written and/or electronic consent.…”
Section: Methodsmentioning
confidence: 99%
“…These disappointments (e.g., making mistakes), losses (e.g., of hoped love) and fears (e.g., of rejection) are all triggers to self-criticism 3,4 . Indeed, self-criticism is a common relating style people use to cope, often resulting in an individual taking the frustration and anger out on themselves, which compounds the experience of pain psychologically and neurophysiologically 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers ultimately advocated increased specification of research targets and additional innovative methods to advance neurophysiological understandings of compassion ( Kim et al, 2020a ). Future research that combines multimodal physiological assessments will be informative for potentially providing convergent evidence about the bidirectional associations between multiple physiological systems important for compassion (e.g., see Nguyen et al, 2016 ; Petrocchi et al, 2017b ; Kim et al, 2020b ). Moreover, future studies combining neuroimaging assessments with behavioral and experience sampling methods will extend the ecological validity, precision, and discriminant validity of existing measures of compassion.…”
Section: Ways Of Knowing Compassionmentioning
confidence: 99%
“…However, more recently, researchers have called into question whether the ratio of HF HRV to LF HRV is an accurate metric for the ratio between sympathetic and parasympathetic activity and identified alternate calculations of vagal tone as a more accurate reflection of the underlying physiology ( Heathers, 2014 ). HF HRV and the root mean-square of successive differences have both been used in recent research as a measure of autonomic control of the heart, mediated by the vagus nerve ( Matos et al, 2017 ; Petrocchi et al, 2017a ; Kim et al, 2020b ).…”
Section: Ways Of Knowing Compassionmentioning
confidence: 99%